2015
DOI: 10.1186/1475-2891-14-1
|View full text |Cite
|
Sign up to set email alerts
|

A randomized longitudinal dietary intervention study during pregnancy: effects on fish intake, phospholipids, and body composition

Abstract: Background: Fish and meat intake may affect gestational weight gain, body composition and serum fatty acids. We aimed to determine whether a longitudinal dietary intervention during pregnancy could increase fish intake, affect serum phospholipid fatty acids, gestational weight gain and body composition changes during pregnancy in women of normal weight participating in the Pregnancy Obesity Nutrition and Child Health study. A second aim was to study possible effects in early pregnancy of fish intake and meat i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
130
2
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(139 citation statements)
references
References 55 publications
4
130
2
3
Order By: Relevance
“…Hakim et al reported an IC 50 value of Gelam honey from Malaysia that was 75 mg/mL on HCT-116 cells [34]. Furthermore, using the same honey, the IC 50 values were observed as 39, 80 and 88 mg/mL, respectively, on other colon cancer cells by a different research group [31,32,33]. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hakim et al reported an IC 50 value of Gelam honey from Malaysia that was 75 mg/mL on HCT-116 cells [34]. Furthermore, using the same honey, the IC 50 values were observed as 39, 80 and 88 mg/mL, respectively, on other colon cancer cells by a different research group [31,32,33]. …”
Section: Resultsmentioning
confidence: 99%
“…Only a few studies have evaluated the anticancer activity of honey on human colon cancer in vitro by targeting the different molecular mechanisms [29,30,31,32,33,34]. Among these, only one study reported the cytotoxic effect of MH on colon cancer and, to date, there are no data on the biological effects of STH on cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Las unidades de análisis según el ámbito geográfico de procedencia muestran un predominio de investigaciones provenientes de Asia (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23) seguidas por las experiencias de América del Norte (24-34), Europa (35)(36)(37)(38)(39)(40)(41)(42), América Latina (43-49) y en menor medida las procedentes de Oceanía (50-51) y África (52-53).…”
Section: Resultsunclassified
“…Bosaeus M. y cols. 2015 (35) Suecia El consumo semanal de pescado aumentó en el GI, desde el primer al segundo trimestre (p= 0,03) y desde el segundo al tercer trimestre (p= 0,01). En el primer trimestre el consumo de pescado se correlacionó con los valores serológicos de EPA (r= 0,36, p= 0,002) y de DHA (r= 0,34, p= 0,005) y el consumo de carne se correlacionó con los valores serológicos de ARA (r= 0,28, p= 0,02).…”
Section: Características De Las Estrategias Educativas Empleadasunclassified
See 1 more Smart Citation